2021
DOI: 10.1136/bmjopen-2020-045630
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness and influencing factors regarding hepatitis B and hepatitis C in Chongqing municipality and Chengdu City, China: a cross-sectional study with community residents

Abstract: ObjectiveHepatitis B and hepatitis C cause a heavy disease burden in China. This paper aims to investigate the public’s knowledge on hepatitis B and hepatitis C in Chongqing municipality and Chengdu City, China.DesignA cross-sectional study was conducted from December 2016 to April 2017.SettingTwo communities from Chongqing and Chengdu were involved in this study.ParticipantsData from 928 community residents were analysed.OutcomeDemographic characteristics, knowledge on hepatitis B and hepatitis C and sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…15,16 Yet, inadequate HBV and HCV testing uptake and related hepatitis testing stigma are persistent barriers to early testing, vaccination and treatment initiation. 11,17 Moreover, patients often become lost in the Chinese healthcare system without obtaining appropriate testing and treatment. To maintain the progress made towards achieving the national and global goals of reducing viral hepatitis incidence by 90% in 2030, it is imperative to routinely assess the effectiveness of programmes that seek to expand HBV and HCV testing to inform policy and implementation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Yet, inadequate HBV and HCV testing uptake and related hepatitis testing stigma are persistent barriers to early testing, vaccination and treatment initiation. 11,17 Moreover, patients often become lost in the Chinese healthcare system without obtaining appropriate testing and treatment. To maintain the progress made towards achieving the national and global goals of reducing viral hepatitis incidence by 90% in 2030, it is imperative to routinely assess the effectiveness of programmes that seek to expand HBV and HCV testing to inform policy and implementation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…21 Slightly lower level of knowledge regarding Hepatitis B and C was found in a study conducted among the general population in China where only 36.1% of their respondents showed sufficient level of knowledge. 22 Awareness on HAV vaccination in our study was moderate (53.6%), and most of the participants knew that personal hygiene is effective in preventing Hepatitis A and E (61%). Our results are consistent with the findings of a study among Malaysian public university students which found that the knowledge regarding vaccination of HAV was moderate (49.2%).…”
Section: Discussionmentioning
confidence: 65%
“…25 Lower level of knowledge regarding HCV curability was found in a study conducted among the general public in China, where only 25.5% of their respondents believed that HCV is curable. 22 For HBV, 49.4% of our participants assumed that it was curable, while 53.9% of participants in the study in Pakistan believed that it is curable up to a certain level. 25 Regarding attitudes toward viral hepatitis, it was found that half of the participants in this study strongly agreed/ agreed that they were willing to deal with someone who has a liver virus.…”
Section: Discussionmentioning
confidence: 77%
“…However, a recent national survey of 200 primary care facilities in China found that only 15% had managed HBV in the preceding month, although 95% of primary care facilities were equipped to provide hepatitis testing services. Creating awareness about the availability of services remains urgent as a significant proportion of participants in our study cited not knowing where to get HCV testing as the main reason for not getting tested 9 . While active provider-initiated services could facilitate testing uptake, previous studies in China and Belgium found that most primary care providers do not offer hepatitis testing services due to limited knowledge and capacity, especially in conducting testing 31 – 33 .…”
Section: Discussionmentioning
confidence: 92%
“…Studies have attributed the low test uptake rates to a lack of awareness and ineffective service promotion strategies 9 , 10 . However, awareness creation strategies still linger on paper-based promotion strategies in most lower/middle-income countries (LMICs), which is costly and has finite reach.…”
Section: Introductionmentioning
confidence: 99%